Clinical Determinants Differentiating the Severity of SARS-CoV-2 Infection in Cancer Patients: Hospital Care or Home Recovery - Lin, Dong D.; Wu, Yunhong; Toom, Sudhamshi; Sheth, Niki; Becker, Kevin; Burdette-Radoux, Susan; D'Silva, James; Huang, Yiwu; Lipshitz, Jay; Meghal, Trishala; Mo, Lan; Murthy, Pooja; et al. (Frontiers in Medicine, 2021)
Background: Cancer patients may carry a worse prognosis with SARS-CoV-2 infection. Most of the previous studies described the outcomes of hospitalized cancer patients. We aimed to study the clinical factors differentiating patients requiring hospital care versus home recovery; and the trajectory of their anti-cancer treatment. Methods: This study was conducted in a community cancer center in New York City. Eligible patients were those who had cancer history and were diagnosed of SARS-CoV-2 infection between March 1 and May 30, 2020, with confirmatory SARs-CoV-2 virus test or antibody test. Four groups were constructed: (A) hospitalized and survived, (B) hospitalized requiring intubation and/or deceased, (C) non-hospitalized, asymptomatic, with suspicious CT image findings, close exposure, or positive antibody test, and (D) non-hospitalized and symptomatic. Results: One hundred and six patients were included in the analysis. Thirty-five patients (33.0%) required hospitalization and 13 (12.3%) died. Thirty (28.3%) patients were asymptomatic and 41 (38.7%) were symptomatic and recovered at home. Comparing to patients who recovered at home, hospitalized patients were composed of older patients (median age 71 vs 63 years old, p=0.000299); received more negative impact treatment (62.9% vs 32.4%, p=0.0036) that mostly represented myelosuppressive chemotherapy (45.7% vs 23.9%, p=0.0275); and had more patients with baseline poor performance status (PS≥2 25.7% vs 2.8%, p=0.0007). Hypoxemia (35% in group A versus 73.3% in group B, p=0.0271) at presentation, was significant to predict mortality in hospitalized patients. The median cumulative hospital stay for discharged patients was 16 days (range 5-60). The median duration of persistent positivity of SARS-CoV-2 RNA was 28 days (range 10-86). About 52.9% of patients who survived hospitalization and required anti-cancer treatment reinitiated therapy. Ninety-two percent of the asymptomatic patients and 51.7% of the symptomatic patients who recovered at home continued treatment on schedule and almost all reinitiated treatment after recovery. Conclusions: Cancer patients may have a more severe status of SARS-CoV-2 infection after receiving therapy with myelosuppressive chemotherapy. Avoidance should be considered in older patients with poor performance status. More than two thirds of patients exhibit minimal to moderate symptoms, and many of them can continue or restart their anti-cancer treatment upon recovery.